Evaluating endoscopic ultrasound-guided tissue acquisition for diagnosis of small pancreatic neuroendocrine neoplasms - Katsuda, Hiromune; Kobayashi, Masanori; Ito, Go; Kawamoto, Ami; Krimura, Susumu; Sato, Hiroyuki; Hirakawa, Akihiro; Akahoshi, Keiichi; Kudo, Atsushi; Ohtsuka, Kazuo; Okamoto, Ryuichi (Endoscopy International Open, 2024)
Background and study aims Although small hypervascular tumors are suspected to be pancreatic neuroendocrine tumors (p-NENs), their diagnosis and treatment are challenging. This study evaluated the usefulness of endoscopic ultrasound-guided tissue acquisition (EUS-TA) for diagnosis of small p-NENs.Methods All p-NEN lesions that underwent EUS-TA at our hospital between April 2018 and December 2023 were retrospectively analyzed. The diagnostic sensitivity of EUS-TA and the concordance rate of grading with EUS-TA and surgical specimens were examined. The lesions were grouped by size.Results The diagnostic sensitivity of EUS-TA was analyzed for 82 lesions, of which 44 were compared with postoperative specimens for grading. The definitive diagnosis was neuroendocrine tumor (NET) in 75 lesions, neuroendocrine carcinoma in five lesions, and mixed neuroendocrine non-neuroendocrine neoplasm in two lesions. Thirty tumors were ≤10 mm, 30 were 10 to 20 mm, and 22 were >20 mm, and the diagnostic sensitivities were 96.7%, 96.7%, and 90.9%, respectively. Concordance rates for grading were 94.4%, 82.4%, and 77.8% for tumors ≤10 mm, 10 to 20 mm, and ≥20 mm, respectively, with Cohen’s kappa coefficients of 0.64, 0.48, and 0.40, respectively.Conclusions EUS-TA showed adequate diagnostic sensitivity and grading agreement for p-NENs of all sizes, allowing for determination of appropriate treatment.
Keywords: Endoscopic ultrasonography; Pancreas; Tissue diagnosis; Fine-needle aspiration/biopsy